2000
DOI: 10.1002/(sici)1098-2418(200003)16:2<156::aid-rsa3>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Random intersection graphs when m=ω(n): An equivalence theorem relating the evolution of the G(n, m, p) and G(n, p) models

Abstract: When the random intersection graph G n m p proposed by Karoński, Scheinerman, and Singer-Cohen [Combin Probab Comput 8 (1999), 131-159] is compared with the independent-edge G n p , the evolutions are different under some values of m and equivalent under others. In particular, when m = n α and α > 6, the total variation distance between the graph random variables has limit 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 0 publications
4
68
0
Order By: Relevance
“…The properties of G(n, m, p) were studied in [2,3] contrasted with the well known random graph model G(n, p), in which vertices are made adjacent to each other independently and with probability p, and showed that for a fixed α > 0, the number of elements m is taken to be m = ⌊n α ⌋. In 1999, Karonski, Scheinerman and Singer-Cohen [2] showed that the total variation distance between the distribution of G(n, m, p) and G(n, p) converges to 0 when α > 6 and p is defined appropriately.…”
Section: Introductionsupporting
confidence: 86%
“…The properties of G(n, m, p) were studied in [2,3] contrasted with the well known random graph model G(n, p), in which vertices are made adjacent to each other independently and with probability p, and showed that for a fixed α > 0, the number of elements m is taken to be m = ⌊n α ⌋. In 1999, Karonski, Scheinerman and Singer-Cohen [2] showed that the total variation distance between the distribution of G(n, m, p) and G(n, p) converges to 0 when α > 6 and p is defined appropriately.…”
Section: Introductionsupporting
confidence: 86%
“…In light of the equivalence theorem proved in [8], it is no surprise that the above result agrees with the well-known result for Erdős-Rényi graphs G(n,p) when α > 6 andp ∼ mp 2 , since the abovementioned equivalence theorem says that, for α > 6 andp ∼ mp 2 , the graphs G(n, m, p) and G(n,p) have asymptotically the same properties. Moreover, this result is consistent with the hypothesis from [8] of the equivalence of the models for α > 3 and their inequivalence for α < 3. From the applied point of view, it would be interesting to obtain similar results for the general random intersection graph models defined as in [9].…”
Section: P(h ⊆ G(n M P)) = 1 If P/τ (H ) → 0 0 If P/τ (H ) → ∞mentioning
confidence: 92%
“…In comparison, for Erdős-Rényi graphs G(n,p), in which edges appear independently and with probabilityp, the bound obtained by Stein's method (presented in Section 2) for the total variation distance between the number of cliques of size h and the Poisson distribution with parameter λ = n h p ( h 2 ) is of order O(n −1 ) for all fixed h ≥ 3 when λ is bounded. In light of the equivalence theorem proved in [8], it is no surprise that the above result agrees with the well-known result for Erdős-Rényi graphs G(n,p) when α > 6 andp ∼ mp 2 , since the abovementioned equivalence theorem says that, for α > 6 andp ∼ mp 2 , the graphs G(n, m, p) and G(n,p) have asymptotically the same properties. Moreover, this result is consistent with the hypothesis from [8] of the equivalence of the models for α > 3 and their inequivalence for α < 3.…”
Section: P(h ⊆ G(n M P)) = 1 If P/τ (H ) → 0 0 If P/τ (H ) → ∞mentioning
confidence: 99%
“…For example, when S is the set of real intervals, one obtains a random interval graph [5,14,21,22]; see Example 2.12 for more. In [10,15,23] one takes S to consist of discrete (finite) sets. Random chordal graphs can be defined by selecting random subtrees of a tree [18].…”
Section: 2mentioning
confidence: 99%